A Rare Case of Metastatic Hepatocellular Carcinoma to the Hard Palate. (October 2022) - Lyon, Priscilla R. P.; Trevathan, Sean; Talukdar, Rudranath; Nguyen, Dominic D.; McPhaul, Christopher M.; Rampisela, Debby
Extrahepatic metastasis of hepatocellular carcinoma (HCC) to the head and neck is unusual, especially the oral cavity/maxillofacial region. Metastatic HCC to the hard palate, however, is particularly rare. The most common site of HCC metastasis is the lung, followed by lymph nodes, bone, and adrenal gland. Importantly, oral cavity metastatic HCC may be misdiagnosed as a primary malignancy, such as a salivary gland carcinoma. In this article, we describe a young woman with metastatic HCC to the hard palate that was initially diagnosed as an acinic cell carcinoma.